(untitled) (Eurasian Journal of Ecology, 2019)
This article provides a systematic list of plants, geobotanical characteristics, cultural and technical condition, economic values and forage reserves of pastures in the Kayrakta rural district of Aitekebi district of Aktobe region. In addition, the geographical location of the study area, topography, water resources, climate and soil cover were fully studied and analyzed. The total number of pastures is determined by districts, and their classification and contours are shown on plant associations. The study revealed 30 types of plant associations, 12 subtypes and 13 modifications. Types are divided into 16 groups, each of which is described individually. Detailed information was obtained on the seasonal use of pastures and the events held there, the total feed stock and its consumption in agriculture. As a result, 88 species from 24 plant families were recorded in the area, 22 of which are eaten by livestock. Among them are eaten or poorly eaten, as well as toxic and medicinal plants. In order to reduce degraded pastures, recommendations were made to improve livestock grazing on 1,030 hectares, reduce pastures on 4,970 hectares and fight weeds on 93 hectares. Based on the results obtained, maps of the study area were mapped and indicators were recorded. Key words: pastures, topography, water resources, soil cover, climate, plant associations, feed stock, livestock grazing, medicinal plants.